Potret Keluarga Sakinah Dalam Keluarga Berpoligami (Dampak Poligami Terhadap Kesejahteraan Anak Dalam Keluarga Di Wilayah Aceh Utara, Indonesia): Dampak Poligami Terhadap Kesejahteraan Anak dalam Keluarga di Wilayah Aceh Utara, Indonesia - Jumala, Nirwani; Zawil, Muhammad (Balai Diklat Keagamaan Surabaya, 2023)
ABSTRACT This study aims to describe the portrait of the Sakinah family in a polygamous family, as well as to reveal the impact of polygamous marriage on children's welfare in North Aceh, Indonesia. This research was conducted using a qualitative approach with field research and library research. Data collection techniques through interviews, observation, and literature studies. Primary data sources were 32 participants consisting of 8 polygamous husbands, 5 first wives, 7-second wives, 1 third wife, 1 fourth wife, and 10 children in polygamous families. Secondary data sources from the field consisted of Islamic religious counsellors who served at the KUA, and community leaders in the North Aceh district. The results of this study indicate that respondents define a sakinah family as a comfortable household condition, fulfilling a living both physically and spiritually, as basic needs consisting of food, clothing, shelter, worship, education, affection and fair treatment for all family members. The Sakinah family is also associated with polygamous status, where there are respondents who understand that the Sakinah family is a family that is free from the practice of polygamy. The way polygamy practices affect the well-being of children in the family. Open and legal polygamous marriages have a positive impact on children because husbands/fathers are able to be fair in the family. The relationship between family members is quite harmonious, both the relationship between children and parents, as well as other family members. Meanwhile, secret polygamous marriages tend to have a negative impact on children. Husbands/fathers tend to neglect their responsibilities as heads of the family. The relationship between children and their parents and fellow family members is not always harmonious. The practice of polygamy can affect children's lives in three aspects. Psychologically, polygamous marriage families make children lose confidence, stress or depression, wepping, get angry and hate their parents. In terms of education, children experience a decrease in achievement. The inability of parents to pay school fees causes children to drop out of school. In the social aspect, children who live in a polygamous family experience isolation from friends and get bullying from peers or neighbours. Children also tend to withdraw from social life Keywords: Polygamous Marriage, Sakinah Family, Children’s Life, Aceh Indonesia